Time-space analysis of coverage changes and land use in the Luján River basin (1990-2010) (Huellas, 2022)
This paper performs an analysis of the space-time dynamics of coverage and land use. The study area corresponds to the Luján river basin (Buenos Aires Province, Argentina), and the time period covers 20 years, from 1990 to 2010. It proceeded from the spatial analysis with Geographic Information Systems, using the methodology of change detection, which is based on the cross-tabulation of two maps of different time cuts, and provides a series of indicators that made it possible to measure gains, losses, net and total change, and exchanges between the different categories of analysis defined for the study period. The results obtained point to the development of a diagnosis of the historical evolution of land occupation, as a contribution of Applied Geography to the land use planning of the study area.
Keywords: spatial evolution; change detection; Geographic Information Systems; Luján river Basin